Mabadi Khaira Ummah dan urgensinya di Era Industry 4.0 dan Society 5.0 - Chamidi, Agus Salim; Ulfiah, Ulfiah; Nurjaman, Ujang (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2021)
The 33rd NU Muktamar in Jombang 2015 mandated about 'developing other businesses through collaboration with domestic and foreign parties that benefit the community at large in order to realize the khaira ummah' (AD/ART NU, Article 9). Since the 13th NU Muktamar in Pandeglang 1939, NU has initiated Mabadi' Khaira Ummah (MKU). MKU is the basic principle of forming an ideal society. MKU consists of five basic principles, namely, ash-shidqu (true not lying, trust) al amanah wal-wafa bil 'ahdi (trust, keeping promises, loyal, commitment), at-ta'awun (helping, mutual helping), al adalah (fairness) and al istiqamah (firmness, constancy, consistency). In the midst of the era of industry 4.0 and society 5.0 as it is today, MKU is of course very urgent to provide a harmonious balance so that the goals of industry 4.0 productivity with the human life convenience of society 5.0 in various parts of the world can take place sustainably and full of grace. MKU is also becoming increasingly important alongside the 18 values ​​of character education.